Influência da mata ciliar em parâmetros da ictiocenose e em aspectos populacionais de quatro espécies de peixes em riachos no sul do Brasil - Albrecht, Mariana (Universidade do Vale do Rio dos Sinos, 2012)
The presence or absence of riparian forest is a factor that can influence the quality and availability of food items for fish. The aim of this work is to test the hypothesis if the lateral extension of the riparian forest influences the richness, abundance and diet of fish fauna. By analyzing the stomach content of four fish species Bryconamericus iheringii (Boulenger, 1887), Characidium pterostictum (Gomes, 1947), Heptapterus mustelinus (Valenciennes, 1835) e Rineloricara microlepidogaster (Regan, 1904), it was possible to study their feeding selectivity in order to identify differences and/or consumption patterns in areas with dense riparian vegetation and areas with spare vegetation. The results show evidence for a positive selection for aquatic invertebrates in the diet of fish. However it was not possible to detect differences in the consumption concerning the type of vegetation. No species consumed more than 2% of allochthone material. The failed capture of the influence of the riparian for est on the diet of fish may have been an effect of the spatial scale design at which the work was done. The chemical, hydraulic, morphologic, substrate and associated biologic communities characteristics of the stream are delineated by many landscape factors, which are constrained by different temporal and spatial scales. Studies affirm that the greater the degradation of the watershed, the less explicable will be the internal factors of streams on changes in the community. Therefore it is of utmost importance to determine factors and scales of influence for ictic communities to ensure success in conservation and rehabilitation of water bodies.
Keywords: Mata ciliar; Ictiofauna; Seletividade alimentar; Escala espacial; Riparian vegetation; Ichthyofauna; Feeding selectivity; Spatial scale; ACCNPQ::Ciências Biológicas::Biologia Geral